Recreational drug use and binge drinking: Stimulant but not cannabis intoxication is associated with excessive alcohol consumption - McKetin, Rebecca; Chalmers, J.; Sunderland, M.; Bright, D. (Wiley-Blackwell Publishing Ltd., 2014)
Abstract: Introduction and Aims: Binge drinking is elevated among recreational drug users, but it is not clear whether this elevation is related to intoxication with recreational drugs. We examined whether stimulant intoxication and cannabis intoxication were associated with binge drinking among young adults. Design and Methods: An online survey of 18- to 30-year-old Australians who had drunk alcohol in the past year (n=1994) were quota sampled for: (i) past year ecstasy use (n=497); (ii) past year cannabis (but not ecstasy) use (n=688); and (iii) no ecstasy or cannabis use in the past year (alcohol-only group, n=809). Binge drinking last Saturday night (five or more drinks) was compared for participants who took stimulants (ecstasy, cocaine, amphetamine or methamphetamine) or cannabis last Saturday night. Results: Ecstasy users who were intoxicated with stimulants (n=91) were more likely to binge drink than ecstasy users who were not (n=406) (89% vs. 67%), after adjusting for demographics, poly-drug use and intoxication with cannabis and energy drinks (adjusted odds ratio 3.1, P=0.007), drinking a median of 20 drinks (cf. 10 drinks among other ecstasy users). Cannabis intoxication was not associated with binge drinking among cannabis users (57% vs. 55%) or ecstasy users (73% vs. 71%). Binge drinking was more common in all of these groups than in the alcohol-only group (34%). Discussion and Conclusions: Stimulant intoxication, but not cannabis intoxication, is associated with binge drinking among young adults, compounding already high rates of binge drinking among people who use these drugs.